2014
DOI: 10.1186/s12917-014-0198-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of isoflurane, ketamine-xylazine and a combination of medetomidine, midazolam and fentanyl on physiological variables continuously measured by telemetry in Wistar rats

Abstract: BackgroundThis study investigated effects on cardiovascular parameters during anaesthesia with isoflurane (ISO, 2–3 Vol%), ketamine-xylazine (KX, 100 mg•kg−1 + 5 mg•kg−1) or a combination of medetomidine-midazolam-fentanyl (MMF, 0.15 mg•kg−1 + 2.0 mg•kg−1 + 0.005 mg•kg−1) in rats throughout induction, maintenance and recovery from anaesthesia. Rats were instrumented with a telemetric system for the measurement of systolic, diastolic and mean arterial pressure (SAP, DAP, MAP), pulse pressure (PP), heart rate (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
103
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(113 citation statements)
references
References 34 publications
7
103
0
3
Order By: Relevance
“…The combination of medetomidine, fentanyl and midazolam used for this study has been shown to cause a significant increase in blood pressure in rabbits and rats, which could arise from an increase in vascular resistance or peripheral vasoconstriction, [46,47]. However, it is well-known that the cardiovascular effects of the combination of these anaesthetic agents vary in different species [48] and to the authors' knowledge, there have been no reports on its effect in female FOXnu n1 mice. The increase in HbT and sO 2 in our study can be due to a cardiovascular effect of the anaesthetic agent combination; due to an influence of the hydrodynamic pressure, when the animal is enveloped in a plastic film and submerged inside the water tank; or due to an influence of the compression of the tumour due to the animal's body weight, which possibly stops blood outflow from the tumour.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of medetomidine, fentanyl and midazolam used for this study has been shown to cause a significant increase in blood pressure in rabbits and rats, which could arise from an increase in vascular resistance or peripheral vasoconstriction, [46,47]. However, it is well-known that the cardiovascular effects of the combination of these anaesthetic agents vary in different species [48] and to the authors' knowledge, there have been no reports on its effect in female FOXnu n1 mice. The increase in HbT and sO 2 in our study can be due to a cardiovascular effect of the anaesthetic agent combination; due to an influence of the hydrodynamic pressure, when the animal is enveloped in a plastic film and submerged inside the water tank; or due to an influence of the compression of the tumour due to the animal's body weight, which possibly stops blood outflow from the tumour.…”
Section: Discussionmentioning
confidence: 99%
“…After the recording under the set at 5%, the rat was relieved from anesthesia by removing the nose mask and observed until awakening. Endotracheal intubation in rats requires a certain amount of skill and endoscope for the successful intubation [20] and there were many reports using nose mask for isoflurane anesthesia in rats even in recent years [1, 2, 7, 40]. For practical data using nose mask, we used nose mask instead of endotracheal intubation in maintenance of isoflurane anesthesia.…”
Section: Methodsmentioning
confidence: 99%
“…With regards to post-procedural pain, it could be beneficial to omit naloxone and instead inject buprenorphine, which might antagonise some effects of fentanyl while providing pain alleviation for some hours. However, to date the protocol of Henke and colleagues is often applied in experiments which do not induce longterm substantial pain, but require anaesthesia for immobilizing the animal for a certain time, e.g., for marking, probe sampling, intratracheal instillation, measurements of physiological values (9) , and the many kinds of imaging procedures (e.g., fMRI, PET). For such painless investigations, mice are often subjected to repeated anaesthesia for which a fully reversible anaesthesia protocol might be useful, as (side-) effects of fentanyl are antagonised and prompt recovery from anaesthesia could be provided at a predefined time point.…”
mentioning
confidence: 99%
“…A fully reversible three-component anaesthesia was proposed (7) that has been shown to achieve safe and reliable anaesthesia in chinchillas (6) , ferrets (8) , and rats (9) . This anaesthesia protocol has since been used in mice: Thal and Plesnila (4) administered the anaesthetic mixture in the suggested species-specific dosages (fentanyl 0.05 mg/kg, midazolam 5 mg/kg, medetomidine 0.5 mg/kg) in female C57BL/6 mice.…”
mentioning
confidence: 99%